Autodesk Infraworks and Infraworks 360 essentials - Chappell, Eric 1972- (Sybex, 2014)
Autodesk InfraWorks Essentials is a complete, hands-on tutorial for InfraWorks, the powerful design tool that lets you quickly generate 3D models to create infrastructure designs and proposals. This Autodesk Official Press book shows you the right way to take advantage of versatile InfraWorks features. From creating models in the context of the existing environment to crafting stunning proposals, you'll become comfortable with every step of the design process. After working through this start-to-finish tutorial, you'll be able to productively use InfraWorks for civil project design that's fully integrated with existing real-world characteristics.